2020
DOI: 10.1108/ajems-01-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of employment trend in African agriculture relative to other regions: a gender perspective

Abstract: PurposeLucrative employment in agriculture is fundamental to poverty alleviation in Africa. The paper examined employment along gender, impact of materials and proportion of female employment in African agriculture.Design/methodology/approachTime series econometrics was employed in the framework of production function analysis involving 36 years of data.FindingsResults show that world labour in agriculture decreased from 49.77 to 40.04% but increased from 12.43 to 16.94% in Africa. World female employment in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Related to this, the role of socio-economic conditions appears prevalent in informing not only career choice but also entrepreneurial pursuit (Chinyamurindi, 2020;Hartt, 2018) Ultimately, through South Africa's efforts to encourage new entrants into agriculture, the motivational factors identified in the study appear to encourage a smooth entry into agriculture. The identified motivational factors also appear to link macro-economic stipulations of agriculture's vital role in social and economic development (Mkpado and Mkapado, 2020). An issue to note from the participant stories is how the motivation to agriculture as a career and entrepreneurial pursuit stem from the socio-cultural milieu (Abdoul and Djoulassi, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Related to this, the role of socio-economic conditions appears prevalent in informing not only career choice but also entrepreneurial pursuit (Chinyamurindi, 2020;Hartt, 2018) Ultimately, through South Africa's efforts to encourage new entrants into agriculture, the motivational factors identified in the study appear to encourage a smooth entry into agriculture. The identified motivational factors also appear to link macro-economic stipulations of agriculture's vital role in social and economic development (Mkpado and Mkapado, 2020). An issue to note from the participant stories is how the motivation to agriculture as a career and entrepreneurial pursuit stem from the socio-cultural milieu (Abdoul and Djoulassi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some gaps can be identified in the literature. First, especially on the African continents, attention is being given to agriculture as means of sustenance (Mkpado and Mkapado, 2020). This is actuated by the presence of challenges within the wider economy such as poverty and unemployment (Abdoul and Djoulassi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GMR of 67% implies that for every one Naira invested in agribusiness ventures 67 Kobo covered profits, interests, taxes, and depreciation. This shows that agri-enterpreneurship is a lucrative enterprise in the study area.It was observed that active female participation in agribusinesses across African countries was generally profitable (Alabi et al, 2019;Mkpado and Mkpado, 2020). The BCR and ROI imply that agri-enterpreneurship business outlook is worthwhile and profitable.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, agriculture accounted for 4% of the global Gross Domestic Product (GDP), rising significantly to about 25% of the GDP in the least developing countries (World Bank, 2022). In Sub-Saharan Africa (SSA), agriculture employs more than half of the workforce and therefore plays a critical role in poverty alleviation (OECD, 2016;Mkpado and Mkpado, 2020). However, SSA's agriculture is significantly affected by climate change resulting in prolonged dry spells, drought, heat waves, rising temperatures, cyclones, flooding, irregular rainfall patterns, and increased cases of pests and diseases, all of which affect the overall agriculture production in the region.…”
Section: Introductionmentioning
confidence: 99%